2012
DOI: 10.1002/jts.21656
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' reactions after a wildfire disaster in Greece

Abstract: This cross-sectional study examined the factors associated with higher levels of posttraumatic stress disorder (PTSD) and depression symptoms in 1,468 adolescents, 6 months after a wildfire. The rate of probable PTSD was 29.4% and 20% for probable depression. Findings on predisaster, disaster-related, and postdisaster factors revealed that disaster-related factors-specifically objective and perceived threat to self and others-were associated with symptoms of PTSD but not depression. Predisaster life events, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 30 publications
2
43
0
2
Order By: Relevance
“…In a large adolescent sample reviewed 6 months after an earthquake in China, 24.5% reported clinically significant depressive symptoms and 40.5% reported clinically significant anxiety symptoms. Similar rates of depressive symptoms and anxiety symptoms have been reported after a wildfire in Greece (Papadatou et al, 2012), and somewhat lower rates, that is, 17.6 and 12%, respectively (consistent with data collection, 14 months post-disaster), have been reported following a cyclone in India (Kar & Bastia, 2006). Other posttraumatic presentations include elevated rates of substance abuse (Reijneveld, Crone, Verhulst, & Verloove-Vanhorick, 2003), somatic symptoms (Hensley & Varela, 2008), and aggression (Scheeringa & Zeanah, 2008).…”
Section: Burden Of Child and Youth Mental Health Care Following A Natsupporting
confidence: 77%
“…In a large adolescent sample reviewed 6 months after an earthquake in China, 24.5% reported clinically significant depressive symptoms and 40.5% reported clinically significant anxiety symptoms. Similar rates of depressive symptoms and anxiety symptoms have been reported after a wildfire in Greece (Papadatou et al, 2012), and somewhat lower rates, that is, 17.6 and 12%, respectively (consistent with data collection, 14 months post-disaster), have been reported following a cyclone in India (Kar & Bastia, 2006). Other posttraumatic presentations include elevated rates of substance abuse (Reijneveld, Crone, Verhulst, & Verloove-Vanhorick, 2003), somatic symptoms (Hensley & Varela, 2008), and aggression (Scheeringa & Zeanah, 2008).…”
Section: Burden Of Child and Youth Mental Health Care Following A Natsupporting
confidence: 77%
“…Major depressive disorder is also a common psychiatric disorder which frequently manifests after natural disasters, such as severe earthquakes, hurricanes, and wildfires [14], [20], [39][41]. In this study, we used DSRSC, a common assessment scale of depression, and found that the prevalence rate of depression in our sample was 19.5%.…”
Section: Discussionmentioning
confidence: 83%
“…These include indigenous concerns [33,70,71], examination of different fire management discourses [72-74, 75•, 76], and understanding the physical and mental health impacts of experiencing a wildfire event [54,[77][78][79][80][81][82]. In addition, a number of articles in the Australian literature have begun to explore the role of land use planning in mitigating fire risk [58,83,84] and how gender dynamics can influence preparedness and management dynamics [85,86].…”
Section: Experiencing and Recovering From A Wildfirementioning
confidence: 99%